Household physical activity contributions to total physical activity and its associations with cardiometabolic risk factors: a Brazilian adult population analysis - Luciana L. S. Barboza; Mario R. Azevedo; Danilo R. Silva; Luiz G. Grossi Porto (BMC Public Health)
Abstract Background Physical activity (PA) is well-recognized as a healthy behavior. However, there is insufficient evidence to differentiate the effect of accumulating PA in different PA domains (leisure-time, work, transportation, and household). We analyzed the contribution of household physical activity (HPA) to total physical activity (TPA) and its associations with cardiometabolic risk factors (CMRFs) in Brazilian adults. Methods Data from the 2019 Brazilian National Health Survey were used (n = 87,678). PA variables were constructed based on the weekly time spent on PA in all PA domains. Impact on prevalence, relative contribution of HPA, and Poisson regression models were conducted, reporting proportions and prevalence ratio values with 95%CI. Results When HPA was not considered in TPA, a significant reduction in the prevalence of active individuals was observed (-4.3p.p.), mainly among females (-6.8p.p.). However, the mean contribution of HPA to TPA was small (7.7%). Also, the associations between physical inactivity and CMRFs did not change when including or not HPA. Conclusions In summary, HPA has a modest impact on TPA and in the prevalence of active individuals, especially among females, and, in general, it did not modify the associations between PA and CMRFs.